Process for preparing environment-friendly cloth by utilizing recycled plastic bottles and application

By using technical means such as antibacterial adsorption microspheres and polyelectrolyte flame retardants, the problems of incomplete cleaning and lack of antibacterial flame retardant in the fabrics for recycling plastic bottles are solved, and efficient antibacterial and flame retardant performance is achieved to meet the needs of high-end markets. And comply with environmental protection standards.

CN119321005AActive Publication Date: 2025-01-17SHENZHEN MATERIAL & RECYCLING ENVIRONMENTAL PROTECTION TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411437089.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2025-01-17
Estimated Expiration
2044-10-15

AI Technical Summary

Technical Problem

The existing technology of using recycled plastic bottles to prepare fabrics has problems such as incomplete cleaning and lack of antibacterial and flame retardant capabilities in fibers, which is difficult to meet the needs of the high-end market.

Method used

Antibacterial adsorption microspheres are prepared by calcined mussel shell powder, streptococcin lactate and chitosan, combined with polyelectrolyte flame retardant and compound flame retardant, and regenerated polyester fibers are treated with dopamine modification and nanosilver to form antibacterial Flame retardant fabric.

Benefits of technology

It improves the detergent ability of plastic cleaning agents, enhances the antibacterial and flame retardant properties of fibers, meets the demand of the high-end market, and reduces the release of harmful substances, and meets the requirements of green production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119321005A_ABST
    Figure CN119321005A_ABST
Patent Text Reader

Abstract

The invention provides a process for preparing environment-friendly cloth by utilizing recycled plastic bottles and application, and belongs to the technical field of plastic bottle recycling. The preparation process comprises the following steps: preparing the plastic cleaning agent; preparing a polyelectrolyte flame retardant; preparing regenerated polyester fibers; preparing a compound flame retardant; and preparing the environment-friendly antibacterial flame-retardant cloth. The prepared plastic cleaning agent is used for cleaning recycled plastic bottles, the prepared plastic cleaning agent has good decontamination, emulsification and other capacities, various stains such as oil stains and dust on the surfaces of the plastics can be effectively removed, the cleanliness of the plastics is improved, and the antibacterial adsorption microspheres are added, so that the plastic cleaning agent is environmentally friendly and free of pollution. The cleaning agent has a good adsorption effect on stains, impurities and the like on the plastic surface, and is beneficial to improving the cleaning effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of plastic bottle recycling, and in particular to a process for preparing environmentally friendly fabrics by utilizing recycled plastic bottles and its application. Background Art

[0002] With the continuous improvement of global environmental awareness and the strengthening of resource recycling policies, the recycling of waste plastics, especially polyethylene terephthalate (PET) plastic bottles, has become an important issue in environmental protection and resource conservation. According to statistics, the amount of PET plastic bottle waste generated worldwide each year is huge. If these wastes are not properly handled, they will have a long-term negative impact on the natural environment.

[0003] At present, there are some technologies for making fabrics from recycled plastic bottles. Among them, a common method is to crush and clean the recycled plastic bottles, make them into fibers through a melt spinning process, and then weave the fibers into fabrics. However, this method has some shortcomings. First, the cleaning process of plastic bottles is often not thorough enough, and the residual impurities and bacteria will affect the quality and performance of the fibers. Secondly, since the prepared fabrics are usually polyester fibers made from recycled plastic bottles, their molecular structure is tight and they have no natural antibacterial and flame retardant capabilities. Therefore, they still have certain limitations in terms of breathability, antibacterial, flame retardant and comfort, and it is difficult to meet the needs of the high-end market.

[0004] Therefore, we proposed a process and application of preparing environmentally friendly fabrics using recycled plastic bottles. Summary of the invention

[0005] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a process and application of preparing environmentally friendly fabrics using recycled plastic bottles.

[0006] A process for preparing environmentally friendly fabrics using recycled plastic bottles comprises the following steps:

[0007] S1: Preparation of plastic cleaning agent

[0008] Calcined mussel shell powder, nisin and chitosan are used as raw materials to prepare antibacterial adsorption microspheres, and 10-12 parts by weight of sodium sulfate decahydrate, 1-3 parts by weight of fatty alcohol polyoxyethylene ether, 1-2 parts by weight of sodium dodecyl sulfonate, 3-5 parts by weight of sodium percarbonate, 3-5 parts by weight of sodium perborate, 5-8 parts by weight of citric acid, 15-20 parts by weight of sodium ethylenediaminetetraacetate and 10-12 parts by weight of antibacterial adsorption microspheres are mixed to prepare a plastic cleaning agent;

[0009] S2: Preparation of polyelectrolyte flame retardants

[0010] The polyelectrolyte flame retardant was prepared using chitosan, sodium pyrophosphate and glacial acetic acid as raw materials.

[0011] S3: Preparation of recycled polyester fiber

[0012] The cleaned plastic bottles are crushed to obtain plastic particles, the plastic particles are melted, and plasticizers, stabilizers and polyelectrolyte flame retardants are added, and then spinning is performed to obtain recycled polyester fibers;

[0013] S4: Preparation of compound flame retardant

[0014] hydrolyzing starch under acidic conditions, then mixing the hydrolyzed starch with a phytic acid solution, and mixing the resulting reactant with ammonium polyphosphate to obtain a composite flame retardant;

[0015] S5: Preparation of environmentally friendly antibacterial and flame-retardant fabrics

[0016] Regenerated polyester fibers are modified with dopamine and then placed in a nanosilver solution to obtain antibacterial regenerated polyester fibers. The antibacterial regenerated polyester fibers are immersed in a flame retardant finishing solution at room temperature and then baked to obtain antibacterial flame retardant regenerated polyester fibers. The antibacterial flame retardant regenerated polyester fibers are fed into a loom for weaving to obtain environmentally friendly antibacterial flame retardant fabrics.

[0017] Furthermore, the preparation of the plastic cleaning agent in step S1 specifically comprises the following steps:

[0018] S1.1: clean the discarded mussel shells, remove the shell meat remaining in the shells, soak them in 0.5-1% dilute hydrochloric acid for 30-35 minutes, wash them with distilled water after soaking, dry and crush them, and pass them through a 100-mesh sieve. Put the shell powder after passing the sieve into a muffle furnace and calcine it at 1000-1200°C for 3-4 hours to obtain calcined mussel shell powder;

[0019] S1.2: adding 0.2-0.3 parts by weight of calcined mussel shell powder and 3-5 parts by weight of nisin to 100-120 parts by weight of a 5-8% chitosan aqueous solution, stirring and mixing to obtain a mixed solution, and slowly adding the mixed solution dropwise into a 5-8% calcium chloride aqueous solution with a syringe to form a crude antibacterial adsorption microsphere;

[0020] S1.3: The crude antibacterial adsorbent microspheres were washed with distilled water for 2-3 times, and then immersed in a 0.5-1 mol / L chloroacetic acid solution, and the pH was adjusted to 8-9 with a 0.1-0.2 mol / L sodium hydroxide solution. After curing reaction for 10-12 hours, the antibacterial adsorbent microspheres were washed again with distilled water until neutral, and dried to obtain antibacterial adsorbent microspheres;

[0021] S1.4: Mix and disperse 10-12 parts by weight of sodium sulfate decahydrate, 1-3 parts by weight of fatty alcohol polyoxyethylene ether, 1-2 parts by weight of sodium dodecyl sulfonate, 3-5 parts by weight of sodium percarbonate, 3-5 parts by weight of sodium perborate, 5-8 parts by weight of citric acid, 15-20 parts by weight of sodium ethylenediaminetetraacetate and 10-12 parts by weight of antibacterial adsorption microspheres, stir and disperse, heat to 50-60°C, keep warm for 0.5-3h, and stir at a speed of 100-200r / min to obtain a plastic cleaning agent.

[0022] Furthermore, step S2 of preparing the polyelectrolyte flame retardant specifically comprises the following steps:

[0023] S2.1: Add 4-5 parts by weight of chitosan to 300-400 parts by weight of deionized water, stir and mix, then add 4-5 parts by weight of glacial acetic acid, stir at 60-65° C. for 1-2 hours to obtain a mixed solution I;

[0024] S2.2: adding 5-8 parts by weight of sodium pyrophosphate to 300-400 parts by weight of deionized water, ultrasonically mixing for 20-30 minutes, and then adding glacial acetic acid to adjust the pH to neutral to obtain a mixed solution II;

[0025] S2.3: Place mixed solution I and mixed solution II in a constant pressure dropping funnel respectively, and uniformly add them dropwise into 100-120 parts by weight of deionized water at 40-45°C. Continuously perform magnetic stirring during the dropping process. After the dropping is completed, continue stirring for 1-2 hours, filter to obtain the product, wash the product with deionized water, and dry it to obtain a polyelectrolyte flame retardant.

[0026] Furthermore, step S3 of preparing the regenerated polyester fiber specifically comprises the following steps:

[0027] S3.1: Collect various discarded plastic bottles, classify the plastic bottles according to their materials, manually remove the caps and labels on the polyethylene terephthalate plastic bottles, put the plastic bottles into a cleaning tank, the cleaning tank is filled with plastic cleaning agent, the concentration of the plastic cleaning agent is 3-5%, turn on the ultrasonic cleaning equipment, set the cleaning time to 1-2h, and control the cleaning temperature at 40-50℃;

[0028] S3.2: taking out the cleaned plastic bottles, placing them in a drying device for drying, placing the dried plastic bottles in a grinder for crushing, and screening the crushed plastic particles through a screening device to obtain plastic particles with a particle size of 0.2-0.5 mm;

[0029] S3.3: feeding the screened plastic particles into a melting device, setting the melting temperature to 270-280°C, adding 3-5wt% plasticizer, 2-3wt% stabilizer and 5-8wt% polyelectrolyte flame retardant after the plastic particles are completely melted, and stirring evenly, keeping the plastic melt in the melting device for 2-3h to obtain a melted plastic melt;

[0030] S3.4: The molten plastic melt is sent to the spinning machine through a metering pump for spinning molding. The spinning speed of the spinning machine is set to 200-300m / min, the spinning pressure is adjusted to 20-25MPa, and the spinneret aperture is selected to be 15-20μm. The plastic melt is extruded through the spinneret to form filaments, cooled and solidified in the air, and then stretched and heat-set to obtain recycled polyester fibers.

[0031] Furthermore, step S4 of preparing the compounded flame retardant specifically comprises the following steps:

[0032] S4.1: Add 20-30 parts by weight of starch to 250-300 parts by weight of deionized water, add 1-2 parts by weight of 2.4 mol / L hydrochloric acid under mechanical stirring, react at 40-45°C for 4-5h, then cool to room temperature and filter, wash the filter cake with distilled water, and dry at 40-50°C to constant weight to obtain hydrolyzed starch;

[0033] S4.2: adding 10-12 parts by weight of phytic acid solution to 10-12 parts by weight of deionized water, stirring and mixing, and then adding sodium carbonate to adjust the pH to neutral to obtain a phytic acid mixed solution;

[0034] S4.3: Add 10-12 parts by weight of hydrolyzed starch to 20-30 parts by weight of deionized water, stir and mix, then drop the above-mentioned phytic acid mixed solution, and then react at 45-50°C for 5-6 hours. After cooling to room temperature, filter, wash and dry to obtain phytic acid starch fat. Mix the phytic acid starch fat and ammonium polyphosphate in a mass ratio of 1:1 to obtain a compound flame retardant.

[0035] Furthermore, step S5 of preparing the environmentally friendly antibacterial flame-retardant fabric specifically includes the following steps:

[0036] S5.1: Prepare 0.5M Tris buffer, add dopamine hydrochloride powder into the Tris buffer solution to prepare a dopamine buffer with an amine concentration of 2.5-3mmol / L, place the regenerated polyester fiber in the dopamine buffer, and shake it in a water bath at 30-35°C for 20-24h to obtain dopamine-modified regenerated polyester fiber;

[0037] S5.2: prepare a 40-50 mmol / L nanosilver solution, place the dopamine-modified regenerated polyester fiber in the nanosilver solution, and shake it in a 30-35° C. water bath for 20-24 hours to obtain an antibacterial regenerated polyester fiber;

[0038] S5.3: Add 5-8 parts by weight of the compound flame retardant to 30-50 parts by weight of deionized water, and then react with magnetic stirring at 40-50° C. for 30-40 minutes to obtain a flame retardant finishing liquid;

[0039] S5.4: Immerse the antibacterial regenerated polyester fiber in the flame retardant finishing solution at room temperature for 40-50 minutes, then put it into an ultrasonic cleaning machine for 15-20 minutes, and after completion, put the antibacterial regenerated polyester fiber into a vacuum drying oven at 70-80° C. and bake it for 1-2 hours to obtain the antibacterial flame retardant regenerated polyester fiber;

[0040] S5.5: The antibacterial flame-retardant recycled polyester fiber is fed into a loom for weaving. After the weaving is completed, it is inspected and sorted to remove the stray hair and defects on the surface to obtain an environmentally friendly antibacterial flame-retardant fabric.

[0041] Furthermore, the plasticizer in step S3.2 is dioctyl phthalate.

[0042] Furthermore, in step S3.3, the stabilizer is calcium stearate.

[0043] Furthermore, in step S4.1, the starch is potato starch.

[0044] A use of environmentally friendly fabric prepared by a process for preparing environmentally friendly fabric using recycled plastic bottles, wherein the environmentally friendly fabric is used for preparing fire-fighting clothing.

[0045] Compared with the prior art, the present invention has at least the following beneficial effects:

[0046] 1. The present invention prepares a plastic cleaning agent for cleaning recycled plastic bottles. The plastic cleaning agent prepared by the present invention has good decontamination and emulsification capabilities, can effectively remove various stains on the plastic surface, such as oil stains, dust, etc., improve the cleanliness of the plastic, and is added with antibacterial adsorption microspheres, which have a good adsorption effect on stains, impurities, etc. on the plastic surface, help to improve the cleaning effect, and can adsorb and remove tiny particles, organic matter and other pollutants on the plastic surface, making the plastic surface cleaner. Due to the addition of nisin and specially treated mussel shell powder, the prepared antibacterial adsorption microspheres are added to the cleaning agent to effectively inhibit the growth and reproduction of bacteria on the plastic surface, have good antibacterial effect, reduce the cumbersome steps of using a variety of single-function cleaning agents, and improve cleaning efficiency and quality.

[0047] 2. The present invention adds a polyelectrolyte flame retardant during the preparation of the regenerated polyester fiber. The sodium pyrophosphate in the polyelectrolyte flame retardant contains a plurality of phosphate ions. The phosphate ions can decompose to produce metaphosphoric acid and other substances when heated, which can promote the dehydration and carbonization of the material surface to form a dense carbon layer. The polymer chain structure of chitosan will interact with the formed carbon layer during the combustion process to enhance the stability of the carbon layer, thereby preventing the transfer of heat and oxygen, playing a flame retardant effect, and improving the self-extinguishing performance of the regenerated polyester fiber. In addition, the amino groups in the chitosan and the phosphate ions in the sodium pyrophosphate can interact with each other by ionic bonding to form a polyelectrolyte structure, so that a stable network structure is formed inside the fiber, thereby enhancing the thermal stability and anti-aging performance of the regenerated polyester fiber and extending the service life. The selected chitosan and sodium pyrophosphate are both relatively environmentally friendly substances. Compared with traditional halogen or phosphorus flame retardants, the release of harmful substances is reduced, which meets the requirements of modern green production.

[0048] 3. The present invention forms a polydopamine film on the surface of the recycled polyester fiber by self-polymerization, and uses dopamine to load nano-silver particles, which gives the recycled polyester fiber antibacterial properties, can effectively kill and inhibit bacterial growth, and ensure the hygienic safety of the fabric during long-term use. After that, the fabric is impregnated and baked with a flame retardant finishing liquid. The ammonium polyphosphate in the composite flame retardant will decompose and produce ammonia and phosphoric acid and other substances when heated. Ammonia can dilute the oxygen concentration in the surrounding air and play a role in inhibiting combustion. Phosphoric acid can promote the dehydration and carbonization of the material surface to form a carbon layer. Hydrolyzed starch and phytic acid starch fat can form a carbon layer during the combustion process. The carbon layer of phytic acid starch can further enhance the stability of the carbon layer formed by ammonium polyphosphate, and the substances produced by the decomposition of ammonium polyphosphate can also enhance the flame retardant effect of phytic acid starch. Therefore, the use of compound flame retardants provides multiple flame retardant mechanisms for recycled polyester fibers, effectively inhibits the spread of flames, reduces the heat release rate, and improves the fire safety of materials. The use of bio-based material potato starch as one of the flame retardant components and the use of an environmentally friendly self-polymerization method to form a polydopamine film reduces the harmful substances that may be contained in traditional flame retardants and antibacterial agents, which meets the requirements of sustainable development and environmental protection. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] The accompanying drawings, which are incorporated herein and constitute a part of the specification, illustrate embodiments of the invention and, together with the description, further serve to explain the principles of the invention and to enable those skilled in the relevant art to make and use the invention.

[0050] Figure 1 This is a process flow chart of preparing environmentally friendly fabrics using recycled plastic bottles adopted in an embodiment of the present invention. DETAILED DESCRIPTION

[0051] The following is a detailed description of a process for preparing environmentally friendly fabrics using recycled plastic bottles provided by the present invention in conjunction with the accompanying drawings and specific embodiments. At the same time, it is explained here that in order to make the embodiments more detailed, the following embodiments are the best and preferred embodiments, and those skilled in the art may also adopt other alternative methods to implement some known technologies; and the accompanying drawings are only for more specific description of the embodiments, and are not intended to specifically limit the present invention.

[0052] Example 1

[0053] A process for preparing environmentally friendly fabrics using recycled plastic bottles, such as Figure 1 As shown, the following steps are included:

[0054] S1: Preparation of plastic cleaning agent

[0055] S1.1: clean the discarded mussel shells, remove the shell meat remaining in the shells, soak them in 0.5% dilute hydrochloric acid for 30 minutes, wash them with distilled water after soaking, dry and crush them, and pass them through a 100-mesh sieve. Put the shell powder after passing the sieve into a muffle furnace and calcine it at 1000°C for 3 hours to obtain calcined mussel shell powder;

[0056] S1.2: Add 0.2 parts by weight of calcined mussel shell powder and 3 parts by weight of nisin to 100 parts by weight of a 5% chitosan aqueous solution, stir and mix evenly to obtain a mixed solution, and slowly add the mixed solution dropwise into a 5% calcium chloride aqueous solution with a syringe to form a crude antibacterial adsorption microsphere;

[0057] S1.3: The crude antibacterial adsorbent microspheres were washed twice with distilled water, and then immersed in a 0.5 mol / L chloroacetic acid solution, and the pH was adjusted to 8 with a 0.1 mol / L sodium hydroxide solution. After curing reaction for 10 h, the antibacterial adsorbent microspheres were washed again with distilled water until neutral, and dried to obtain antibacterial adsorbent microspheres;

[0058] S1.4: 10 parts by weight of sodium sulfate decahydrate, 1 part by weight of fatty alcohol polyoxyethylene ether, 1 part by weight of sodium dodecyl sulfate, 3 parts by weight of sodium percarbonate, 3 parts by weight of sodium perborate, 5 parts by weight of citric acid, 15 parts by weight of sodium ethylenediaminetetraacetate and 10 parts by weight of antibacterial adsorption microspheres are mixed and dispersed by stirring, heated to 50° C., kept warm for 0.5 h, and stirred at a speed of 100 r / min to obtain a plastic cleaning agent;

[0059] S2: Preparation of polyelectrolyte flame retardants

[0060] S2.1: 4 parts by weight of chitosan were added to 300 parts by weight of deionized water, and after stirring, 4 parts by weight of glacial acetic acid were added, and the mixture was stirred at 60° C. for 1 h to obtain a mixed solution I;

[0061] S2.2: 5 parts by weight of sodium pyrophosphate were added to 300 parts by weight of deionized water, and ultrasonically mixed for 20 minutes, and then glacial acetic acid was added to adjust the pH to neutral to obtain a mixed solution II;

[0062] S2.3: The mixed solution I and the mixed solution II are placed in a constant pressure dropping funnel respectively, and are uniformly added dropwise to 100 parts by weight of deionized water at 40°C, and magnetic stirring is continuously performed during the dropping process. After the dropping is completed, stirring is continued for 1 hour, and the product is filtered to obtain the product. The product is washed with deionized water and dried to obtain a polyelectrolyte flame retardant;

[0063] S3: Preparation of recycled polyester fiber

[0064] S3.1: Collect various discarded plastic bottles, classify the plastic bottles according to their materials, manually remove the caps and labels on the polyethylene terephthalate plastic bottles, put the plastic bottles into a cleaning tank, the cleaning tank is filled with a plastic cleaning agent with a concentration of 3%, turn on the ultrasonic cleaning equipment, set the cleaning time to 1h, and control the cleaning temperature at 40℃;

[0065] S3.2: taking out the cleaned plastic bottles, placing them in a drying device for drying, placing the dried plastic bottles in a grinder for crushing, and screening the crushed plastic particles through a screening device to obtain plastic particles with a particle size of 0.2 mm;

[0066] S3.3: The screened plastic particles are fed into a melting device, the melting temperature is set to 270°C, and when the plastic particles are completely melted, 3wt% of plasticizer dioctyl phthalate, 2wt% of stabilizer calcium stearate and 5wt% of polyelectrolyte flame retardant are added and stirred evenly, and the plastic melt is kept in the melting device for 2 hours to obtain a melted plastic melt;

[0067] S3.4: The molten plastic melt is fed into a spinning machine through a metering pump for spinning and forming. The spinning speed of the spinning machine is set to 200 m / min, the spinning pressure is adjusted to 20 MPa, and the spinneret aperture is selected to be 15 μm. The plastic melt is extruded through the spinneret to form a filament, cooled and solidified in the air, and then stretched and heat-set to obtain the regenerated polyester fiber.

[0068] S4: Preparation of compound flame retardant

[0069] S4.1: 20 parts by weight of potato starch are added to 250 parts by weight of deionized water, 1 part by weight of 2.4 mol / L hydrochloric acid is added under mechanical stirring, and the mixture is reacted at 40°C for 4 hours, and then cooled to room temperature and filtered, the filter cake is washed with distilled water, and dried at 40°C to constant weight to obtain hydrolyzed starch;

[0070] S4.2: adding 10 parts by weight of phytic acid solution to 10 parts by weight of deionized water, stirring and mixing, and then adding sodium carbonate to adjust the pH to neutral to obtain a phytic acid mixed solution;

[0071] S4.3: 10 parts by weight of hydrolyzed starch are added to 20 parts by weight of deionized water, and the above phytic acid mixed solution is added dropwise after stirring and mixing, and then reacted at 45°C for 5 hours. After cooling to room temperature, the mixture is filtered, washed and dried to obtain phytic acid starch fat, and the phytic acid starch fat and ammonium polyphosphate are mixed uniformly in a mass ratio of 1:1 to obtain a composite flame retardant;

[0072] S5: Preparation of environmentally friendly antibacterial and flame-retardant fabrics

[0073] S5.1: Prepare 0.5M Tris buffer, add dopamine hydrochloride powder into the Tris buffer solution to prepare a dopamine buffer with an amine concentration of 2.5mmol / L, place the regenerated polyester fiber in the dopamine buffer, and shake it in a 30℃ water bath for 20h to obtain dopamine-modified regenerated polyester fiber;

[0074] S5.2: Prepare a 40 mmol / L nanosilver solution, place the dopamine-modified regenerated polyester fiber in the nanosilver solution, and shake it in a 30°C water bath for 20 hours to obtain the antibacterial regenerated polyester fiber;

[0075] S5.3: Add 5 parts by weight of the compound flame retardant to 30 parts by weight of deionized water, and then react with magnetic stirring at 40° C. for 30 minutes to obtain a flame retardant finishing liquid;

[0076] S5.4: The antibacterial regenerated polyester fiber is immersed in the flame retardant finishing liquid at room temperature for 40 minutes, and then placed in an ultrasonic cleaning machine for 15 minutes. After completion, the antibacterial regenerated polyester fiber is placed in a vacuum drying oven and baked at 70° C. for 1 hour to obtain the antibacterial flame retardant regenerated polyester fiber;

[0077] S5.5: The antibacterial flame-retardant recycled polyester fiber is fed into a loom for weaving. After the weaving is completed, it is inspected and sorted to remove the stray hair and defects on the surface to obtain an environmentally friendly antibacterial flame-retardant fabric.

[0078] Example 2

[0079] A process for preparing environmentally friendly fabrics using recycled plastic bottles, such as Figure 1 As shown, the following steps are included:

[0080] S1: Preparation of plastic cleaning agent

[0081] S1.1: clean the discarded mussel shells, remove the shell meat remaining in the shells, soak them in 1% dilute hydrochloric acid for 30 minutes, wash them with distilled water after soaking, dry and crush them, and pass them through a 100-mesh sieve. Put the shell powder after passing the sieve into a muffle furnace and calcine it at 1000°C for 3 hours to obtain calcined mussel shell powder;

[0082] S1.2: 0.3 parts by weight of calcined mussel shell powder and 5 parts by weight of nisin are added to 120 parts by weight of an 8% chitosan aqueous solution, and the mixture is stirred and mixed to obtain a mixed solution, and the mixed solution is slowly added dropwise to an 8% calcium chloride aqueous solution using a syringe to form a crude antibacterial adsorption microsphere;

[0083] S1.3: The crude antibacterial adsorbent microspheres were washed twice with distilled water, and then immersed in a 1 mol / L chloroacetic acid solution, and the pH was adjusted to 9 with a 0.2 mol / L sodium hydroxide solution. After curing reaction for 10 h, the antibacterial adsorbent microspheres were washed again with distilled water until neutral, and dried to obtain antibacterial adsorbent microspheres;

[0084] S1.4: 12 parts by weight of sodium sulfate decahydrate, 3 parts by weight of fatty alcohol polyoxyethylene ether, 2 parts by weight of sodium dodecyl sulfonate, 5 parts by weight of sodium percarbonate, 5 parts by weight of sodium perborate, 8 parts by weight of citric acid, 20 parts by weight of sodium ethylenediaminetetraacetate and 12 parts by weight of antibacterial adsorption microspheres are mixed and dispersed by stirring, heated to 50° C., kept warm for 0.5 h, and stirred at a speed of 100 r / min to obtain a plastic cleaning agent;

[0085] S2: Preparation of polyelectrolyte flame retardants

[0086] S2.1: 5 parts by weight of chitosan was added to 400 parts by weight of deionized water, and after stirring, 5 parts by weight of glacial acetic acid was added, and stirred at 60° C. for 1 h to obtain a mixed solution I;

[0087] S2.2: 8 parts by weight of sodium pyrophosphate were added to 400 parts by weight of deionized water, and ultrasonically mixed for 20 minutes, and then glacial acetic acid was added to adjust the pH to neutral to obtain a mixed solution II;

[0088] S2.3: The mixed solution I and the mixed solution II are placed in a constant pressure dropping funnel respectively, and are uniformly added dropwise to 120 parts by weight of deionized water at 40°C, with continuous magnetic stirring during the addition process. After the addition is completed, stirring is continued for 1 hour, and the product is filtered to obtain the product. The product is washed with deionized water and dried to obtain a polyelectrolyte flame retardant;

[0089] S3: Preparation of recycled polyester fiber

[0090] S3.1: Collect various discarded plastic bottles, classify the plastic bottles according to their materials, manually remove the caps and labels on the polyethylene terephthalate plastic bottles, put the plastic bottles into a cleaning tank, the cleaning tank is filled with a plastic cleaning agent with a concentration of 5%, turn on the ultrasonic cleaning equipment, set the cleaning time to 1h, and control the cleaning temperature at 40℃;

[0091] S3.2: taking out the cleaned plastic bottles, placing them in a drying device for drying, placing the dried plastic bottles in a grinder for crushing, and screening the crushed plastic particles through a screening device to obtain plastic particles with a particle size of 0.2 mm;

[0092] S3.3: feeding the screened plastic particles into a melting device, setting the melting temperature to 270°C, adding 5wt% of plasticizer dioctyl phthalate, 3wt% of stabilizer calcium stearate and 8wt% of polyelectrolyte flame retardant after the plastic particles are completely melted, stirring evenly, and keeping the plastic melt in the melting device for 2 hours to obtain a melted plastic melt;

[0093] S3.4: The molten plastic melt is fed into a spinning machine through a metering pump for spinning and forming. The spinning speed of the spinning machine is set to 200 m / min, the spinning pressure is adjusted to 20 MPa, and the spinneret aperture is selected to be 15 μm. The plastic melt is extruded through the spinneret to form a filament, cooled and solidified in the air, and then stretched and heat-set to obtain the regenerated polyester fiber.

[0094] S4: Preparation of compound flame retardant

[0095] S4.1: 30 parts by weight of potato starch are added to 300 parts by weight of deionized water, and 1-2 parts by weight of 2.4 mol / L hydrochloric acid are added under mechanical stirring, and the mixture is reacted at 40°C for 4 hours, and then cooled to room temperature and filtered, the filter cake is washed with distilled water, and dried at 40°C to constant weight to obtain hydrolyzed starch;

[0096] S4.2: adding 12 parts by weight of phytic acid solution to 12 parts by weight of deionized water, stirring and mixing, and then adding sodium carbonate to adjust the pH to neutral to obtain a phytic acid mixed solution;

[0097] S4.3: 12 parts by weight of hydrolyzed starch are added to 30 parts by weight of deionized water, and the above phytic acid mixed solution is added dropwise after stirring and mixing, and then reacted at 45°C for 5 hours. After cooling to room temperature, the mixture is filtered, washed and dried to obtain phytic acid starch fat, and the phytic acid starch fat and ammonium polyphosphate are mixed uniformly in a mass ratio of 1:1 to obtain a composite flame retardant;

[0098] S5: Preparation of environmentally friendly antibacterial and flame-retardant fabrics

[0099] S5.1: Prepare 0.5M Tris buffer, add dopamine hydrochloride powder into the Tris buffer solution to prepare a dopamine buffer with an amine concentration of 3mmol / L, place the regenerated polyester fiber in the dopamine buffer, and shake it in a 30℃ water bath for 20h to obtain dopamine-modified regenerated polyester fiber;

[0100] S5.2: Prepare a 50 mmol / L nanosilver solution, place the dopamine-modified regenerated polyester fiber in the nanosilver solution, and shake it in a 30°C water bath for 20 hours to obtain the antibacterial regenerated polyester fiber;

[0101] S5.3: 8 parts by weight of the compound flame retardant is added to 50 parts by weight of deionized water, and then reacted with magnetic stirring at 40° C. for 30 minutes to obtain a flame retardant finishing liquid;

[0102] S5.4: The antibacterial regenerated polyester fiber is immersed in the flame retardant finishing liquid at room temperature for 40 minutes, and then placed in an ultrasonic cleaning machine for 15 minutes. After completion, the antibacterial regenerated polyester fiber is placed in a vacuum drying oven and baked at 70° C. for 1 hour to obtain the antibacterial flame retardant regenerated polyester fiber;

[0103] S5.5: The antibacterial flame-retardant recycled polyester fiber is fed into a loom for weaving. After the weaving is completed, it is inspected and sorted to remove the stray hair and defects on the surface to obtain an environmentally friendly antibacterial flame-retardant fabric.

[0104] Example 3

[0105] A process for preparing environmentally friendly fabrics using recycled plastic bottles, such as Figure 1 As shown, the following steps are included:

[0106] S1: Preparation of plastic cleaning agent

[0107] S1.1: clean the discarded mussel shells, remove the shell meat remaining in the shells, soak them in 0.5% dilute hydrochloric acid for 35 minutes, wash them with distilled water after soaking, dry and crush them, and pass them through a 100-mesh sieve. Put the shell powder after passing the sieve into a muffle furnace and calcine it at 1200°C for 4 hours to obtain calcined mussel shell powder;

[0108] S1.2: Add 0.2 parts by weight of calcined mussel shell powder and 3 parts by weight of nisin to 100 parts by weight of a 5% chitosan aqueous solution, stir and mix evenly to obtain a mixed solution, and slowly add the mixed solution dropwise into a 5% calcium chloride aqueous solution with a syringe to form a crude antibacterial adsorption microsphere;

[0109] S1.3: The crude antibacterial adsorbent microspheres were washed with distilled water for 3 times, and then immersed in a 0.5 mol / L chloroacetic acid solution, and the pH was adjusted to 8 with a 0.2 mol / L sodium hydroxide solution. After curing reaction for 12 hours, the antibacterial adsorbent microspheres were washed again with distilled water until neutral, and dried to obtain antibacterial adsorbent microspheres;

[0110] S1.4: 10 parts by weight of sodium sulfate decahydrate, 1 part by weight of fatty alcohol polyoxyethylene ether, 1 part by weight of sodium dodecyl sulfate, 3 parts by weight of sodium percarbonate, 3 parts by weight of sodium perborate, 5 parts by weight of citric acid, 15 parts by weight of sodium ethylenediaminetetraacetate and 10 parts by weight of antibacterial adsorption microspheres are mixed and dispersed by stirring, heated to 60° C., kept warm for 3 h, and stirred at a speed of 200 r / min to obtain a plastic cleaning agent;

[0111] S2: Preparation of polyelectrolyte flame retardants

[0112] S2.1: 4 parts by weight of chitosan were added to 300 parts by weight of deionized water, and after stirring, 4 parts by weight of glacial acetic acid were added, and the mixture was stirred at 65° C. for 2 h to obtain a mixed solution I;

[0113] S2.2: 5 parts by weight of sodium pyrophosphate were added to 300 parts by weight of deionized water, and ultrasonically mixed for 30 minutes, and then glacial acetic acid was added to adjust the pH to neutral to obtain a mixed solution II;

[0114] S2.3: The mixed solution I and the mixed solution II are placed in a constant pressure dropping funnel respectively, and are uniformly added dropwise to 100 parts by weight of deionized water at 45°C, and magnetic stirring is continuously performed during the dropping process. After the dropping is completed, stirring is continued for 2 hours, and the product is filtered to obtain the product. The product is washed with deionized water and dried to obtain a polyelectrolyte flame retardant;

[0115] S3: Preparation of recycled polyester fiber

[0116] S3.1: Collect various discarded plastic bottles, classify the plastic bottles according to their materials, manually remove the caps and labels on the polyethylene terephthalate plastic bottles, put the plastic bottles into a cleaning tank, the cleaning tank is filled with a plastic cleaning agent with a concentration of 3%, turn on the ultrasonic cleaning equipment, set the cleaning time to 2 hours, and control the cleaning temperature at 50°C;

[0117] S3.2: taking out the cleaned plastic bottles, placing them in a drying device for drying, placing the dried plastic bottles in a grinder for crushing, and screening the crushed plastic particles through a screening device to obtain plastic particles with a particle size of 0.5 mm;

[0118] S3.3: The screened plastic particles are fed into a melting device, the melting temperature is set to 280°C, and when the plastic particles are completely melted, 3wt% of plasticizer dioctyl phthalate, 2wt% of stabilizer calcium stearate and 5wt% of polyelectrolyte flame retardant are added and stirred evenly, and the plastic melt is kept in the melting device for 3 hours to obtain a melted plastic melt;

[0119] S3.4: The molten plastic melt is fed into a spinning machine through a metering pump for spinning and forming. The spinning speed of the spinning machine is set to 300 m / min, the spinning pressure is adjusted to 25 MPa, and the spinneret aperture is selected to be 20 μm. The plastic melt is extruded through the spinneret to form a filament, cooled and solidified in the air, and then stretched and heat-set to obtain the regenerated polyester fiber.

[0120] S4: Preparation of compound flame retardant

[0121] S4.1: 20 parts by weight of potato starch are added to 250 parts by weight of deionized water, 1 part by weight of 2.4 mol / L hydrochloric acid is added under mechanical stirring, and the mixture is reacted at 45°C for 5 hours, and then cooled to room temperature and filtered, the filter cake is washed with distilled water, and dried at 50°C to constant weight to obtain hydrolyzed starch;

[0122] S4.2: adding 10 parts by weight of phytic acid solution to 10 parts by weight of deionized water, stirring and mixing, and then adding sodium carbonate to adjust the pH to neutral to obtain a phytic acid mixed solution;

[0123] S4.3: 12 parts by weight of hydrolyzed starch are added to 20 parts by weight of deionized water, and the above phytic acid mixed solution is added dropwise after stirring and mixing, and then reacted at 50°C for 6 hours. After cooling to room temperature, the mixture is filtered, washed and dried to obtain phytic acid starch grease, and the phytic acid starch grease and ammonium polyphosphate are mixed uniformly in a mass ratio of 1:1 to obtain a composite flame retardant;

[0124] S5: Preparation of environmentally friendly antibacterial and flame-retardant fabrics

[0125] S5.1: Prepare 0.5M Tris buffer, add dopamine hydrochloride powder into the Tris buffer solution to prepare a dopamine buffer with an amine concentration of 2.5mmol / L, place the regenerated polyester fiber in the dopamine buffer, and shake it in a 35℃ water bath for 24h to obtain dopamine-modified regenerated polyester fiber;

[0126] S5.2: Prepare a 40 mmol / L nanosilver solution, place the dopamine-modified regenerated polyester fiber in the nanosilver solution, and shake it in a 35°C water bath for 24 hours to obtain the antibacterial regenerated polyester fiber;

[0127] S5.3: Add 5 parts by weight of the compound flame retardant to 30 parts by weight of deionized water, and then react with magnetic stirring at 50° C. for 40 minutes to obtain a flame retardant finishing liquid;

[0128] S5.4: The antibacterial regenerated polyester fiber is immersed in the flame retardant finishing liquid at room temperature for 50 minutes, and then placed in an ultrasonic cleaning machine for 20 minutes. After completion, the antibacterial regenerated polyester fiber is placed in a vacuum drying oven and baked at 80° C. for 2 hours to obtain the antibacterial flame retardant regenerated polyester fiber;

[0129] S5.5: The antibacterial flame-retardant recycled polyester fiber is fed into a loom for weaving. After the weaving is completed, it is inspected and sorted to remove the stray hair and defects on the surface to obtain an environmentally friendly antibacterial flame-retardant fabric.

[0130] The environmentally friendly antibacterial flame retardant fabrics of Examples 1-3 were subjected to performance tests, and the test results are shown in Table 1.

[0131] Antibacterial test: According to the test method GB / T20944.3-2008 "Evaluation of antibacterial properties of textiles Part 3: Oscillation method", the number of colonies was recorded to calculate the antibacterial rate.

[0132] Table 1. Antibacterial performance test results of Examples 1-3

[0133] Antibacterial rate (%) Example 1 99.93 Example 2 99.89 Example 3 99.91

[0134] Flame retardancy test: According to GB / T5455-2014 “Determination of vertical damage length, smoldering and afterflaming time of textile combustion performance”, the afterflaming, smoldering time and damage length of each sample were recorded.

[0135] Table 2. Flame retardant performance test results of Examples 1-3

[0136] Afterburning time(s) Smoldering time(s) Damaged length(cm) Example 1 0 0 4.8 Example 2 0 0 5.3 Example 3 0 0 5.1

[0137] Antistatic performance test: Use YG(B)406 fabric resistivity tester to measure the surface resistance of environmentally friendly antibacterial flame retardant fabrics.

[0138] Substituting the surface resistance value R into the formula ρ=R×L / ω, the surface resistivity of the environmentally friendly antibacterial flame-retardant fabric is obtained (L represents the effective circumference of the protected electrode 0.16m, ω represents the distance between the two electrodes 0.02m).

[0139] Table 3. Antistatic performance test results of Examples 1-3

[0140] Surface resistivity(Ω) Example 1 <![CDATA[8.84×10 8 ]]> Example 2 <![CDATA[8.86×10 8 ]]> Example 3 <![CDATA[8.87×10 8 ]]>

[0141] Air permeability test: Use YG461E-III fully automatic air permeability meter to conduct air permeability test based on ENISO9237-1995 "Determination of air permeability of textile fiber fabrics".

[0142] Table 4. Test results of air permeability of Examples 1-3

[0143] Air permeability (mm / s) Example 1 2198.3 Example 2 2093.4 Example 3 2120.3

[0144] Washing resistance test: refer to AATCC61-2013 "Color fastness to washing: accelerated method" (method 2A) to conduct washing resistance test. After each washing process, rinse the sample with distilled water at 40℃ and then conduct antibacterial performance test.

[0145] Table 5. Test results of washability of Examples 1-3

[0146] Antibacterial rate after 4 washes (%) Example 1 90.96 Example 2 89.59 Example 3 90.36

[0147] It can be seen from the data in Tables 1 to 5 that the environmentally friendly, antibacterial and flame-retardant fabric prepared by the present invention has good comprehensive performance and is a multifunctional fabric that combines protection and comfort while using green and environmentally friendly materials.

[0148] Comparative Example 1

[0149] Compared with Example 1, the difference of Comparative Example 1 is that the polyelectrolyte flame retardant in step S2 and step S3.3 is removed in Comparative Example 1, and the other steps remain unchanged to prepare the environmentally friendly antibacterial flame retardant fabric, which is recorded as Comparative Example 1.

[0150] Comparative Example 2

[0151] Compared with Example 1, the difference of Comparative Example 2 is that Comparative Example 2 removes step S4 and steps S5.3-S5.4, replaces the antibacterial flame retardant regenerated polyester fiber in step S5.5 with antibacterial regenerated polyester fiber, and the other steps remain unchanged to prepare an environmentally friendly antibacterial flame retardant fabric, which is recorded as Comparative Example 2.

[0152] The data of Example 1 was used to carry out flame retardancy test on Comparative Examples 1-2. The test results are shown in Table 6.

[0153] Table 6. Flame retardant performance test results of Example 1 and Comparative Examples 1-2

[0154] Afterburning time(s) Smoldering time(s) Damaged length(cm) Example 1 0 0 4.8 Comparative Example 1 0.7 1.4 8.2 Comparative Example 2 1.2 1.9 10.3

[0155] It can be seen from the data in Table 6 that the present invention can effectively inhibit the combustion process of recycled polyester fibers by adding polyelectrolyte flame retardants, and through the use of compound flame retardants, multiple flame retardant mechanisms are provided for recycled polyester fibers, which further effectively inhibit the spread of flames. Through the dual effects of polyelectrolyte flame retardants and compound flame retardants, the flame retardant properties of environmentally friendly antibacterial flame retardant fabrics are effectively improved.

[0156] Comparative Example 3

[0157] Compared with Example 1, the difference of Comparative Example 3 is that Comparative Example 3 removes steps S5.1-S5.2, replaces the antibacterial regenerated polyester fiber in step S5.4 with regenerated polyester fiber, and the other steps remain unchanged to prepare the environmentally friendly antibacterial flame-retardant fabric, which is recorded as Comparative Example 3.

[0158] The data of Example 1 was used to test the antibacterial performance of Comparative Example 3. The test results are shown in Table 7.

[0159] Table 7. Antibacterial performance test results of Example 1 and Comparative Example 3

[0160] Antibacterial rate (%) Example 1 99.93 Comparative Example 3 68.39

[0161] From the data in Table 7, it can be seen that a polydopamine film is self-polymerized on the surface of the recycled polyester fiber, and the dopamine is used to load the nanosilver particles, giving the environmentally friendly antibacterial and flame-retardant fabric antibacterial properties.

[0162] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.

Claims

1. A process for preparing environmentally friendly fabrics using recycled plastic bottles, characterized in that: The steps include: S1: Preparation of plastic cleaning agent Calcined mussel shell powder, nisin and chitosan are used as raw materials to prepare antibacterial adsorption microspheres, and 10-12 parts by weight of sodium sulfate decahydrate, 1-3 parts by weight of fatty alcohol polyoxyethylene ether, 1-2 parts by weight of sodium dodecyl sulfonate, 3-5 parts by weight of sodium percarbonate, 3-5 parts by weight of sodium perborate, 5-8 parts by weight of citric acid, 15-20 parts by weight of sodium ethylenediaminetetraacetate and 10-12 parts by weight of antibacterial adsorption microspheres are mixed to prepare a plastic cleaning agent; S2: Preparation of polyelectrolyte flame retardants The polyelectrolyte flame retardant was prepared using chitosan, sodium pyrophosphate and glacial acetic acid as raw materials. S3: Preparation of recycled polyester fiber The cleaned plastic bottles are crushed to obtain plastic particles, the plastic particles are melted, and plasticizers, stabilizers and polyelectrolyte flame retardants are added, and then spinning is performed to obtain recycled polyester fibers; S4: Preparation of compound flame retardant hydrolyzing starch under acidic conditions, then mixing the hydrolyzed starch with a phytic acid solution, and mixing the resulting reactant with ammonium polyphosphate to obtain a composite flame retardant; S5: Preparation of environmentally friendly antibacterial and flame-retardant fabrics Regenerated polyester fibers are modified with dopamine and then placed in a nanosilver solution to obtain antibacterial regenerated polyester fibers. The antibacterial regenerated polyester fibers are immersed in a flame retardant finishing solution at room temperature and then baked to obtain antibacterial flame retardant regenerated polyester fibers. The antibacterial flame retardant regenerated polyester fibers are fed into a loom for weaving to obtain environmentally friendly antibacterial flame retardant fabrics.

2. The process for preparing environmentally friendly fabrics using recycled plastic bottles according to claim 1, characterized in that: Step S1: Preparation of plastic cleaning agent, specifically comprising the following steps: S1.1: clean the discarded mussel shells, remove the shell meat remaining in the shells, soak them in 0.5-1% dilute hydrochloric acid for 30-35 minutes, wash them with distilled water after soaking, dry and crush them, and pass them through a 100-mesh sieve. Put the shell powder after passing the sieve into a muffle furnace and calcine it at 1000-1200°C for 3-4 hours to obtain calcined mussel shell powder; S1.2: adding 0.2-0.3 parts by weight of calcined mussel shell powder and 3-5 parts by weight of nisin to 100-120 parts by weight of a 5-8% chitosan aqueous solution, stirring and mixing to obtain a mixed solution, and slowly adding the mixed solution dropwise into a 5-8% calcium chloride aqueous solution with a syringe to form a crude antibacterial adsorption microsphere; S1.3: The crude antibacterial adsorbent microspheres were washed with distilled water for 2-3 times, and then immersed in a 0.5-1 mol / L chloroacetic acid solution, and the pH was adjusted to 8-9 with a 0.1-0.2 mol / L sodium hydroxide solution. After curing reaction for 10-12 hours, the antibacterial adsorbent microspheres were washed again with distilled water until neutral, and dried to obtain antibacterial adsorbent microspheres; S1.4: Mix and disperse 10-12 parts by weight of sodium sulfate decahydrate, 1-3 parts by weight of fatty alcohol polyoxyethylene ether, 1-2 parts by weight of sodium dodecyl sulfonate, 3-5 parts by weight of sodium percarbonate, 3-5 parts by weight of sodium perborate, 5-8 parts by weight of citric acid, 15-20 parts by weight of sodium ethylenediaminetetraacetate and 10-12 parts by weight of antibacterial adsorption microspheres, stir and disperse, heat to 50-60°C, keep warm for 0.5-3h, and stir at a speed of 100-200r / min to obtain a plastic cleaning agent.

3. The process for preparing environmentally friendly fabrics using recycled plastic bottles according to claim 1, characterized in that: Step S2: Preparation of polyelectrolyte flame retardant, specifically comprising the following steps: S2.1: Add 4-5 parts by weight of chitosan to 300-400 parts by weight of deionized water, stir and mix, then add 4-5 parts by weight of glacial acetic acid, stir at 60-65° C. for 1-2 hours to obtain a mixed solution I; S2.2: adding 5-8 parts by weight of sodium pyrophosphate to 300-400 parts by weight of deionized water, ultrasonically mixing for 20-30 minutes, and then adding glacial acetic acid to adjust the pH to neutral to obtain a mixed solution II; S2.3: Place mixed solution I and mixed solution II in a constant pressure dropping funnel respectively, and uniformly add them dropwise into 100-120 parts by weight of deionized water at 40-45°C. Continuously perform magnetic stirring during the dropping process. After the dropping is completed, continue stirring for 1-2 hours, filter to obtain the product, wash the product with deionized water, and dry it to obtain a polyelectrolyte flame retardant.

4. The process for preparing environmentally friendly fabrics using recycled plastic bottles according to claim 1, characterized in that: Step S3: Preparation of regenerated polyester fiber, specifically comprising the following steps: S3.1: Collect various discarded plastic bottles, classify the plastic bottles according to their materials, manually remove the caps and labels on the polyethylene terephthalate plastic bottles, put the plastic bottles into a cleaning tank, the cleaning tank is filled with plastic cleaning agent, the concentration of the plastic cleaning agent is 3-5%, turn on the ultrasonic cleaning equipment, set the cleaning time to 1-2h, and control the cleaning temperature at 40-50℃; S3.2: taking out the cleaned plastic bottles, placing them in a drying device for drying, placing the dried plastic bottles in a grinder for crushing, and screening the crushed plastic particles through a screening device to obtain plastic particles with a particle size of 0.2-0.5 mm; S3.3: feeding the screened plastic particles into a melting device, setting the melting temperature to 270-280°C, adding 3-5wt% plasticizer, 2-3wt% stabilizer and 5-8wt% polyelectrolyte flame retardant after the plastic particles are completely melted, and stirring evenly, keeping the plastic melt in the melting device for 2-3h to obtain a melted plastic melt; S3.4: The molten plastic melt is sent to the spinning machine through a metering pump for spinning molding. The spinning speed of the spinning machine is set to 200-300m / min, the spinning pressure is adjusted to 20-25MPa, and the spinneret aperture is selected to be 15-20μm. The plastic melt is extruded through the spinneret to form filaments, cooled and solidified in the air, and then stretched and heat-set to obtain recycled polyester fibers.

5. The process for preparing environmentally friendly fabrics using recycled plastic bottles according to claim 1, characterized in that: Step S4 is the preparation of the compound flame retardant, which specifically comprises the following steps: S4.1: Add 20-30 parts by weight of starch to 250-300 parts by weight of deionized water, add 1-2 parts by weight of 2.4 mol / L hydrochloric acid under mechanical stirring, react at 40-45°C for 4-5h, then cool to room temperature and filter, wash the filter cake with distilled water, and dry at 40-50°C to constant weight to obtain hydrolyzed starch; S4.2: adding 10-12 parts by weight of phytic acid solution to 10-12 parts by weight of deionized water, stirring and mixing, and then adding sodium carbonate to adjust the pH to neutral to obtain a phytic acid mixed solution; S4.3: Add 10-12 parts by weight of hydrolyzed starch to 20-30 parts by weight of deionized water, stir and mix, then drop the above-mentioned phytic acid mixed solution, and then react at 45-50°C for 5-6 hours. After cooling to room temperature, filter, wash and dry to obtain phytic acid starch fat. Mix the phytic acid starch fat and ammonium polyphosphate in a mass ratio of 1:1 to obtain a compound flame retardant.

6. The process for preparing environmentally friendly fabrics using recycled plastic bottles according to claim 1, characterized in that: Step S5 is the preparation of the environmentally friendly antibacterial flame-retardant fabric, which specifically includes the following steps: S5.1: Prepare 0.5M Tris buffer, add dopamine hydrochloride powder into the Tris buffer solution to prepare a dopamine buffer with an amine concentration of 2.5-3mmol / L, place the regenerated polyester fiber in the dopamine buffer, and shake it in a water bath at 30-35°C for 20-24h to obtain dopamine-modified regenerated polyester fiber; S5.2: prepare a 40-50 mmol / L nanosilver solution, place the dopamine-modified regenerated polyester fiber in the nanosilver solution, and shake it in a 30-35° C. water bath for 20-24 hours to obtain an antibacterial regenerated polyester fiber; S5.3: Add 5-8 parts by weight of the compound flame retardant to 30-50 parts by weight of deionized water, and then react with magnetic stirring at 40-50° C. for 30-40 minutes to obtain a flame retardant finishing liquid; S5.4: Immerse the antibacterial regenerated polyester fiber in the flame retardant finishing solution at room temperature for 40-50 minutes, then put it into an ultrasonic cleaning machine for 15-20 minutes, and after completion, put the antibacterial regenerated polyester fiber into a vacuum drying oven at 70-80° C. and bake it for 1-2 hours to obtain the antibacterial flame retardant regenerated polyester fiber; S5.5: The antibacterial flame-retardant recycled polyester fiber is fed into a loom for weaving. After the weaving is completed, it is inspected and sorted to remove the stray hair and defects on the surface to obtain an environmentally friendly antibacterial flame-retardant fabric.

7. The process for preparing environmentally friendly fabrics using recycled plastic bottles according to claim 4, characterized in that: The plasticizer in step S3.2 is dioctyl phthalate.

8. The process for preparing environmentally friendly fabrics using recycled plastic bottles according to claim 4, characterized in that: The stabilizer in step S3.3 is calcium stearate.

9. The process for preparing environmentally friendly fabrics using recycled plastic bottles according to claim 5, characterized in that: The starch in step S4.1 is potato starch.

10. Use of the environmentally friendly fabric prepared by the process of preparing environmentally friendly fabric by recycling plastic bottles according to claims 1-9, characterized in that: The environmentally friendly fabric is used for preparing fire-fighting clothing.

Citation Information

Patent Citations

  • Antibacterial flame-retardant polyester fiber master batch, fiber and preparation method of antibacterial flame-retardant polyester fiber master batch

    CN117364263A

  • Antibacterial fire retardancy recycled polyester filament for interior and method thereof

    KR1020110118445A

  • Flame-retardant antistatic regenerated polyester wig fiber and preparation method thereof

    US20240023657A1